Damage characteristics and distribution patterns of invasive pest, Spodoptera frugiperda (J.E Smith) (Lepidoptera: Noctuidae) on maize crop in Bali, Indonesia - I WAYAN Supartha; I WAYAN SUSILA; ANAK AGUNG AYU AGUNG SRI SUNARI; I. G. FEBRI MAHAPUTRA; I KADEK WISMA YUDHA; PUTU ANGGA WIRADANA (Society for Indonesian Biodiversity, 2021)
Abstract. Supartha IW, Susila IW, Sunari AAAAS, Mahaputra IGF, Yudha IKW, Wiradana PA. 2021. Damage characteristics and distribution patterns of invasive pest, Spodoptera frugiperda (J.E Smith) (Lepidoptera: Noctuidae) on maize crop in Bali, Indonesia. Biodiversitas 22: 3378-3387. The Fall Armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae) is a destructive crop pest native to North and South America which has now been reported to have spread to Indonesia. This study aims to ensure the attack and spread of invasive pests FAW on corn crops in Bali. In addition, it also studied population structure, age structure, and percentage of attacks on maize crops in high altitude areas in Bali, Indonesia. The research was conducted using survey methods. A sampling of plants is carried out in all districts and cities in the Province of Bali by diagonal sampling. The sample unit size is 5 m × 5 m with the number of plants observed being 150 plants. The score of plant damage at the age of 4 weeks after planting (WAP) plants has a